FATIGUE LIFE PREDICTION OF BASALT- CARBON HYBRID COMPOSITE FOR WIND TURBINE ROTOR BLADES - MENGAL, ALI NAWAZ (2016)
Modem wind turbine blade sizes are increasing, and the driving motivation behind this is to increase the efficiency and energy output per unit rotor area. However, due to the increase in size, the material selection for wind turbine has become critical and complex. Fatigue resistance of composite materials used in wind turbine rotor blades has been recognized as a major uncertainty in predicting the reliability of wind turbines over their design lifetime. The main challenges related to existing wind turbine rotor blade materials are low fatigue resistance, low compressive strength, low ultimate strain and high cost. To overcome these issues, research is needed to introduce new materials for wind turbine rotor blades. With this aim, in the present work, fatigue life of basalt-carbon/epoxy hybrid composite was studied on different lay-ups and the potential of this new hybrid composite was analyzed for wind turbine rotor blades. Six symmetrical lamination stacking sequences with eight layers of unidirectional 0° and biaxial ± 45° were selected for the current study.